2016
DOI: 10.22159/ijpps.2017v9i1.15397
|View full text |Cite
|
Sign up to set email alerts
|

Assess the Knowledge and Practice of Reproductive Aged Tribal Women on Family Welfare Methods

Abstract: Objective: Family welfare program has met with only marginal success due to different levels of awareness and acceptance of methods of family planning in various socioeconomic groups. Unmet needs of family planning are more in tribal population of the country. With this background the study was done to assess the knowledge and practice of family welfare methods among tribal women and to associate the knowledge of family welfare methods with the selected demographic variables. Methods:A community based descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…With a total of 200 women aged between 15 and 45 years revealed that almost 94% population had inadequate knowledge on family planning. The study also revealed that there is no correlation between the risk factors such as age, religion, etc., and family welfare [22]. Likewise, JF and SP have a higher significant in the Irula tribes.…”
Section: Discussionmentioning
confidence: 92%
“…With a total of 200 women aged between 15 and 45 years revealed that almost 94% population had inadequate knowledge on family planning. The study also revealed that there is no correlation between the risk factors such as age, religion, etc., and family welfare [22]. Likewise, JF and SP have a higher significant in the Irula tribes.…”
Section: Discussionmentioning
confidence: 92%
“…Our finding was much higher compared to studies conducted in Bangladesh, Nepal, urban India, rural India, and Ethiopia, in which the level of knowledge of postpartum women on prevention of puerperal infection was 39.3%, 36.73%, 35%, 30%, and 12.6%, respectively. [15][16][17][18][19] Another study that was conducted in India reported that postnatal mothers had moderate knowledge regarding prevention of puerperal sepsis. 20 The reason for the difference observed in the level of knowledge may be contributed to the variation in the number of ANC visits across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Use of contraceptive methods are influenced by various factors. Health-care provider should find the unmet needs of individual women to find suitable family planning methods [12].…”
Section: Discussionmentioning
confidence: 99%